2019
DOI: 10.1016/j.jcte.2019.100203
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic variability is associated with adverse cardiovascular outcomes in patients hospitalised with an acute myocardial infarction

Abstract: Unlike admission hyperglycaemia, there is significant controversy surrounding whether acute glycaemic variability is associated with major adverse cardiovascular events (MACE) in patients immediately after an acute myocardial infarction (AMI). We conducted a retrospective post-hoc analysis in an AMI population and determined fluctuating glycaemia is associated with a higher risk of 3–month MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The final analysis included 11 studies which met the inclusion criteria for meta-analysis. [15][16][17][18][19][20][21][22][23][24][25]…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…The final analysis included 11 studies which met the inclusion criteria for meta-analysis. [15][16][17][18][19][20][21][22][23][24][25]…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…The characteristics of the included studies were showed in Table 1. Overall, 11 prospective studies with 3709 ACS patients were included in this meta-analysis, of which six studies included patients with acute myocardial infarction, [15][16][17][18][19]24 five included patients with ACS. [20][21][22][23]25 The studies were all performed in China, Japan, Australia and France, with sample sizes varying from 34 to 864.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiovascular complications are the main cause of death in diabetic patients [ 7 , 8 ]. Previous studies showed that admission hyperglycemia was an independent risk factor for poor prognosis of ACS patients, irrespective of whether or not they had diabetes [ 9 , 10 ]. Pasquale first showed that hyperglycemia was associated with adverse outcomes and increased risk of restenosis in ST-elevation myocardial infarction patients without diabetes mellitus [ 11 ].…”
Section: Discussionmentioning
confidence: 99%